Application Of Double Exponential Smoothing Holt’s Method For Poverty Line Forecasting (Study Case: East Kalimantan Province) - Ariantika Putri Maharani; Akhmad Irsyad; Muhammad Rivani Ibrahim (ULTIMATICS, 2025)
Poverty is a multidimensional problem that remains a challenge in Indonesia. The poverty line is used as an indicator to determine whether someone is poor based on the average expenditure per capita per month. In East Kalimantan Province, the poverty line has increased from Rp796,193 in 2023 to Rp853,997 in 2024. This study aims to forecast the poverty line for the next ten periods using Holt's Double Exponential Smoothing method. This method was chosen because the historical data shows an increasing trend from 2011 to 2024. The forecasting results show that this method is effective with a Mean Absolute Percentage Error (MAPE) value of 4.56%, and optimal parameters α = 0.98 and β = 0.01. The findings are expected to serve as a reference in decision-making regarding poverty alleviation policies in the future.